1995
DOI: 10.1056/nejm199512213332502
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Lamivudine, Zidovudine, or Both in HIV-Positive Patients with 200 to 500 CD4+ Cells per Cubic Millimeter

Abstract: In HIV-infected patients with little or no prior antiretroviral therapy, treatment with a combination of lamivudine and zidovudine is well tolerated over a one-year period and produces more improvement in immunologic and virologic measures than does treatment with either agent alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
215
0
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(234 citation statements)
references
References 43 publications
12
215
0
7
Order By: Relevance
“…This conclusion is supported by earlier studies of lamivudine, which demonstrated greater and more durable responses to lamivudine plus zidovudine in terms of CD4-count increases and viral-load decreases in patients who had received no previous antiretroviral treatment, than in patients who had received previous zidovudine therapy. [5][6][7][8] These data together support the conclusion that a combination of lamivudine plus zidovudine will provide the greatest clinical benefit to patients who have not previously received other antiretroviral therapies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This conclusion is supported by earlier studies of lamivudine, which demonstrated greater and more durable responses to lamivudine plus zidovudine in terms of CD4-count increases and viral-load decreases in patients who had received no previous antiretroviral treatment, than in patients who had received previous zidovudine therapy. [5][6][7][8] These data together support the conclusion that a combination of lamivudine plus zidovudine will provide the greatest clinical benefit to patients who have not previously received other antiretroviral therapies.…”
Section: Discussionsupporting
confidence: 53%
“…[1][2][3][4] Combination treatment with lamivudine (Glaxo Wellcome) plus zidovudine (Glaxo Wellcome) caused pronounced and sustained increases in CD4-cell counts and reductions in HIV-1 viral load in four separate studies, done in both previously antiretroviral untreated and pretreated HIV-1-positive patients. [5][6][7][8] Meta-analysis of these four studies showed that these treatment-induced changes in CD4 count and viral load were associated with a reduction in disease progression. 9 Because these studies were done in relatively healthy patients (CD4 range 100-500/µL) the majority of clinical events included in this meta-analysis were the development of Centers for Disease Control and Prevention Stage B (CDC B) AIDSrelated complex events in patients who were symptom free at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Similar changes have been described in two other shortterm, virological-endpoint trials studying combinations of two nucleoside reverse-transcriptase inhibitors. 20,21 The Wellcome Resistance Study Collaboration Group 22 followed a similar protocol to Delta 1 (with half the didanosine dose) and also found only a low frequency of both resistant mutations and isolates with decreased susceptibility to didanosine and zalcitabine in the combined-therapy groups. There were no differences found in the evolution of zidovudine mutations at codon 215 in the three treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lamivudine administered orally, it is rapidly absorbed with a bioavailability of 80% to 87%. FDA approval granted in 1995 for lamivudine to use pediatric and adult based on increases in CD4 T-lymphocyte count [8] on a regimen of zidovudine and lamivudine compared with either drug alone or compared with a combination of zalcitabine and zidovudine was initial approval [9]. Lamivudine is in combinations with several triple nucleoside analogues has been shown to lead to high virologic failure in previously untreated individuals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%